2020
DOI: 10.1097/jcma.0000000000000424
|View full text |Cite
|
Sign up to set email alerts
|

Visiting in disguise: Analysis of inpatient companions in the time of COVID-19

Abstract: Background: As outbreak of COVID-19 infection, on April 3, 2020, it is stipulated that the number of inpatient companions is limited to one in Taiwan. All companions are required to register their real personal data with 14 days of travel history, occupation, contact history, and cluster history. We would like to evaluate the impact of the new regulations to the accompanying and visiting culture in Taiwan, via analyzing the appearance and characteristics of inpatient companions in this period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…In our study, the number of nursing hours increased during the pandemic, possibly due to the vacancy periods of inpatient companions who had to wait for the PCR test results. Nursing staff assisted throughout the process, thus increasing the number of daily nursing hours, which is consistent with the literature [ 9 , 11 ]. The primary inpatient companions were 862 males (36.96%) and 1273 females (54.59%).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In our study, the number of nursing hours increased during the pandemic, possibly due to the vacancy periods of inpatient companions who had to wait for the PCR test results. Nursing staff assisted throughout the process, thus increasing the number of daily nursing hours, which is consistent with the literature [ 9 , 11 ]. The primary inpatient companions were 862 males (36.96%) and 1273 females (54.59%).…”
Section: Discussionsupporting
confidence: 88%
“…The primary inpatient companions were 862 males (36.96%) and 1273 females (54.59%). The results of this analysis are consistent with the survey results of the Republic of China Family Caregivers Association, which found that most inpatient companions are female [ 7 , 9 , 25 ]. The total scores for patients with inpatient companions were higher than those for patients without inpatient companions both before and during the pandemic period.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations